Aberrant Promoter Methylation of PTEN Gene among Indian Patients with Oral Squamous Cell Carcinoma. Issue 3 (July 2013) - Alyasiri, Nisreen S.; Ali, Asgar; Kazim, Zakia; Gupta, Sunita; Mandal, Ashish K.; Singh, Ishwar; Rizvi, Moshahid A.
Background and aims: Oral cancer is the second most common cancer in men and accounts for 50%-70% of the total cancer mortality in India. PTEN is a tumor suppressor gene that plays a critical role in controlling cell growth and survival. Promoter hypermethylation of the PTEN gene has been reported in many tumors. However, little is known about the association between promoter methylation and oral squamous cell carcinoma (OSCC). Therefore, we aimed to detect the role of PTEN hypermethylation in OSCC patients in the Indian population. Methods: Genomic DNA was isolated from 100 fresh oral tumor specimens and was subjected to bisulfite conversion. Methylation-specific PCR was employed on the converted DNA to investigate the methylation status. Results: Of the total cases examined for PTEN promoter methylation we found that 35% were positive and 65% were negative. When evaluated in connection with tumor differentiation it was found that 82% of poorly differentiated, 24% of moderately differentiated and 32% of well differentiated OSCC samples were methylated. Methylation was further correlated with patient age, sex and tumor grade. Interestingly, we found that patient age and grade of differentiation were significantly associated with PTEN promoter methylation (p=0.05 and 0.0019, respectively) while sex was not (p=0.9). Conclusions: The present study underlines the importance of PTEN hypermethylation among Indian OSCC patients.